Redox gated polymer memristive processing memory unit - Zhang, Bin; Fan, Fei; Xue, Wuhong; Liu, Gang; Fu, Yubin; Zhuang, Xiaodong; Xu, Xiao-Hong; Gu, Junwei; Li, Run-Wei; Chen, Yu (Nature communications, 2019)
Memristors with enormous storage capacity and superior processing efficiency are of critical importance to overcome the Moore’s Law limitation and von Neumann bottleneck problems in the big data and artificial intelligence era. In particular, the integration of multifunctionalities into a single memristor promises an essential strategy of obtaining a high-performance electronic device that satisfies the nowadays increasing demands of data storage and processing. In this contribution, we report a proof-of-concept polymer memristive processing-memory unit that demonstrates programmable information storage and processing capabilities. By introducing redox active moieties of triphenylamine and ferrocene onto the pendants of fluorene skeletons, the conjugated polymer exhibits triple oxidation behavior and interesting memristive switching characteristics. Associated with the unique electrochemical and electrical behavior, the polymer device is capable of executing multilevel memory, decimal arithmetic operations of addition, subtraction, multiplication and division, as well as simple Boolean logic operations. Though designing conductive polymers for memory devices is attractive for future low-cost flexible electronics, a proof-of-concept device has yet to be realized. Here, the authors report a redox-gated polymer memristive processing unit with programmable multilevel storage and logic functionalities.